PENGARUH PRAKTEK SUMBERDAYA MANUSIA, ORGANIZATIONAL CITIZENSHIP BEHAVIOR, DAN KEADILAN ORGANISASI TERHADAP KINERJA ORGANISASI BISNIS RESTORAN DI INDONESIA - Sahban, Hernita (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2019)
Currently the restaurant business in Indonesia dealing with tough competition between various sizes of business from within and outside the country. One important factor to improve the performance of this business is the human factor. To explain the human factor in the restaurant business performance, researchers used variables such as human resource management practices, organizational justice, citizenship behavior, and corporate entrepreneurship. The hypothesis was developed based on research results regarding the relationship between these variables. Measurements were performed using data from 106 respondents from the restaurant business in Makassar in July 2013. After item analysis using Confirmatory Factor Analysis (CFA), the analysis was continued using structural equation modeling to test the hypotheses that have been made. Six hypotheses are accepted at p < 0.05 while the remaining four are accepted at p < 0.10.Analysis of the model showed that the model fit indicates a match through a penalty function, meet suitability of parsimony, and stated that the model is acceptable. It is found that justice and corporate entrepreneurship as the most important variables for improving business performance . In contrast to studies on the consumers reasons to choose restaurants based courtesy and kindness are proxied by the citizenship behavior is only significant at the level of p < 0.10. Even so, this variable can be corroborated by justice associated with this variable.Conclusion gives a number of implications that can be used as a concern for restaurant businesses in Indonesia.